Avaliação do BDI em relação aos fatores, métodos e conceitos aplicados em obras públicas na cidade de Campo Mourão-PR - Nascimento, André Luiz do (2014)
The public constructions always have had relevance for Brazilian people, due to the large amount of public money invested and many bid contracts between construction companies and public management. This study aimed to analyze the parameters and opinions of companies and public management about development of BDI rate to the public constructions in the county of Campo Mourão - PR. As this is a qualitative and field research, a questionnaire of seventeen objective questions was developed, had the main function to assist in data collection for completing the project, were interview eight companies and public management. The application that every company has about consideration the questions of the indirect expenses items, became evident, and too the importance that each item has for the calculation of BDI. Had to statement by parts of the companies that in Campo Mourão the average band of the BDI it is between 20% and 30%, coinciding with the public administrator. Obtained that most companies have trouble for calculating the BDI, due to preliminary budget produced by public management, thus making imprecise the calculation of the BDI. In summary, conclude that as much as for companies and public management, there should be more studies on the subject BDI mainly for public works in order to set up a regulatory standard to standardize the method of calculation, avoiding the BDI becomes a set rate and not erroneously calculated.